Reformáció és modernitás - FAZAKAS, Sándor (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2017)
Reformation and Modernity. This lecture endeavors to answer the following questions: In what sense was the 500th anniversary of the reformation different from any previous celebrations? What is the relationship between modernity and the reformation? Does the reformation have a formative role in the contemporary society? This study breaks with the traditional and linear interpretation of modernity and offers reverse methodology, starting from the vantage point of the modern society, and from this angle, examines the religious and theological impulses, and those interfaith dynamics that can have a role in shaping/modeling a peaceful coexistence of cultures and religions. These impulses are: the necessary interaction between various branches of science and religion in the academic setting. The value of the spiritual/theological interpretation of reality in our society. The freedom of conscience and religious thought in the secular state and in the church, and the preservation of self-identity in the age of mass manipulation. Pondering over these issues can and will make our celebration more relevant in the contemporary setting.